At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Simplify the following expression:
-5a + 3b - (-2а) - 7b
Show me how you do it please.


Sagot :

Answer:

- 3a - 4b

Step-by-step explanation:

note that - (- ) = + and + (- ) = -

- 5a + 3b - (- 2a) - 7b

= - 5a + 3b + 2a - 7b ← collect like terms

= (- 5a + 2a) + (3b - 7b)

= - 3a + (- 4b)

= - 3a - 4b